2022
DOI: 10.1007/s41999-022-00731-4
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic dilemmas with benzodiazepines and Z-drugs: insomnia and anxiety disorders versus increased fall risk: a clinical review

Abstract: Purpose The aim of this clinical review was to summarise the existing knowledge on fall risk associated with benzodiazepines (BZDs) and Z-drugs in older people with focus on appropriate prescribing, including deprescribing. Methods We conducted a literature search in June 2021 in PubMed and Embase with citation and reference checking. Personal reference libraries and international websites were also used. Keywords for the searches included “benzodiazepines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 86 publications
1
8
0
Order By: Relevance
“…Common side effects of benzodiazepines and Z-class drugs include headache, dizziness, and daytime sleepiness and drowsiness, and in particular, the elderly are at increased risk of side effects such as cognitive function impairment, delirium, and falls and fractures due to the muscle relaxation effect, although Z-class drugs have relatively fewer side effects compared to benzodiazepines [73]. It is not clear to what extent these sedative hypnotics impact insomnia in postmenopausal women, but considering that older women are more vulnerable to fractures, more caution is needed when prescribing them to older women [74]. Indeed, meta-analyses showed that the use of benzodiazepines or Z-class drugs was associated with an increased risk of falls and fractures in older adults [75,76].…”
Section: Benzodiazepines and Z-class Drugsmentioning
confidence: 99%
“…Common side effects of benzodiazepines and Z-class drugs include headache, dizziness, and daytime sleepiness and drowsiness, and in particular, the elderly are at increased risk of side effects such as cognitive function impairment, delirium, and falls and fractures due to the muscle relaxation effect, although Z-class drugs have relatively fewer side effects compared to benzodiazepines [73]. It is not clear to what extent these sedative hypnotics impact insomnia in postmenopausal women, but considering that older women are more vulnerable to fractures, more caution is needed when prescribing them to older women [74]. Indeed, meta-analyses showed that the use of benzodiazepines or Z-class drugs was associated with an increased risk of falls and fractures in older adults [75,76].…”
Section: Benzodiazepines and Z-class Drugsmentioning
confidence: 99%
“…Consequently, the study ardently advocated the contemplation of non-pharmacological substitutes and proposed the imposition of stringent restrictions on the minimum prescribed dosages and the abbreviated temporal span of drug utilisation. 27 Concerning non-pharmacological interventions, cognitive behavioural therapy for insomnia (CBT-I) stands as one of the more prevalent modalities. 28 Cognitivebehavioural therapy represents a multifaceted therapeutic regimen encompassing sleep education, behavioural interventions, cognitive restructuring and relaxation therapies.…”
Section: Open Accessmentioning
confidence: 99%
“…Importantly, these fall events directly contributed to an amplified mortality risk. Consequently, the study ardently advocated the contemplation of non-pharmacological substitutes and proposed the imposition of stringent restrictions on the minimum prescribed dosages and the abbreviated temporal span of drug utilisation 27…”
Section: Introductionmentioning
confidence: 99%
“…In response to these sleep-related issues, the widespread use of hypnotics, especially benzodiazepines (BZDs), and Z-drug (ZD), has emerged as a common treatment [ 3 ]. Nevertheless, ongoing debates persist regarding the potential long-term consequences of prolonged hypnotics use on health [ 4 - 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…3 Nevertheless, ongoing debates persist regarding the potential long-term consequences of prolonged hypnotics use on health. [4][5][6] In 2019, an approximate 57.4 million individuals across the globe were afflicted by dementia, and prognostications indicated that the incidence of such cases was poised to nearly triple within the ensuing three decades. 7 Modifying several risk factors, like hypertension, obesity, diabetes mellitus and smoking, could help prevent or delay up to 40% of dementias.…”
Section: Introductionmentioning
confidence: 99%